Sitka black-tailed deer (Odocoileus hemionus sitkensis) adjust habitat selection and activity rhythm to the absence of predators - Bonnot, Nadège C; Morellet, Nicolas; Hewison, A.J. Mark; Martin, Jean-Louis; Benhamou, Simon; Chamaillé-Jammes, Simon (Canadian journal of zoology, 2016)
Although individuals must generally trade off acquisition of high-quality resources against predation risk avoidance, removal of top predators by humans has resulted in many large herbivores experiencing novel conditions where their natural predators are absent. Antipredator behaviors should be attenuated or lost in such a context of relaxed predation pressure. To test this prediction, we analyzed daily and seasonal habitat selection and activity rhythm (both commonly linked to predation risk) of GPS-collared Sitka black-tailed deer (Odocoileus hemionus sitkensis Merriam, 1898) on predator-free islands (British Columbia, Canada). In marked contrast to the behavioral patterns commonly observed in populations subject to predation risk, we documented a very low day–night contrast in habitat selection. Moreover, we observed higher activity during daytime than nighttime, as expected for nonhunted populations. We also showed that resource selection was primarily driven by seasonal variations in resource availability. These results are consistent with the expected attenuation of antipredator behaviors in predation-free environments. However, we also observed marked crepuscular activity peaks, which are commonly interpreted as an antipredator response in ungulates. Our study indicates that large herbivores are able to adjust certain antipredator behaviors under relaxed selection, notably habitat selection and activity rhythm, while others persist despite the long-term absence of predators.